Effect of Several Parameters on Membrane Fouling by Using Mathematical Models of Reverse Osmosis Membrane System - Sachit, Dawood Eisa (Al-Nahrain Journal for Engineering Sciences, 2017)
In this paper, models were applied to investigate the parameters that affect membrane fouling. Osmotic pressure across the membrane, salt concentration at the surface of the membrane, solute mass transfer coefficient, effective coefficient diffusion of water, and concentration polarization factor were the main parameters that calculated in this simulation. Sodium chloride was assumed the only salt existed in the feed flux. In addition, changing the applied pressure versus increasing the salt concentration in the feed flux and their effect on the water permeation coefficient was investigated. The results confirmed that concentration polarization gives a good indication about the formation of the fouling layer at the membrane surface and consequently permeate decline.